Response of The Growth and production sweet Corn on the Composition of Planting Media - Tambunan, hon Fiter Fernando; Ginting, Jonis; Meiriani, (Jurnal Online Pertanian Tropik, 2019)
Corn is one of the indicator plants that can give response to volcanic dust sinabung. The purpose of this study was to determine the respons of sweet corn plant growth to the composition of planting media (top soil, Sinabung volcanic dust and EFBOP). This research was done at experimental field of Agriculture Faculty of University of Sumatra Utara, Medan at height about 25 mals in August until November2016. The research was using a non-factorial randomized block design which was consisting of 6 treatments of top soil : volcanic dust : EFBOP ratio that is 10 kg : 0 kg : 0 kg (M0), 8 kg : 0 kg : 2 kg (M1), 8 kg : 0,5 kg : 1,5 kg (M2), 8 kg : 1 kg : 1 kg (M3), 8 kg : 1,5 kg : 0,5 kg (M4), and 8 kg : 2 kg : 0 kg (M5). Parameters observed were plant height, flowering age, length and width of leaves, fresh weights, length of cob, diameter of cob, seed line in cob, and number of seeds of cob. The result showed that the ratio of top soil, Sinabung volcanic dust and EFBOP had significanly effect on plant height, long and width of the leaves, fresh weights, length of cob, diameter of cob, seed line in cob, and number of seeds of cob, and had no significant effect on age flowering. The best composition of planting media was M2 with composition 8 kg top soil, 0,5 kg sinabung volcanic dust, and 1,5 kg EFBOP.